Determinants of Regional Economic Growth in Indonesia - Yuliadi, Imamudin (Universitas Muhammadiyah Yogyakarta, 2020)
The research aims to analyze the effect of exchange rate, length of road, Human Development Index, regional expenditure, domestic investment, foreign investment, and total population on Gross Regional Domestic Product. The analysis used panel data estimation. Data were collected from Bank Indonesia and Statistics Indonesia (BPS) from 2010 to 2016. This research employed econometrics analysis in order to obtain the estimation result of the regional economic model in Indonesia that matched with statistics and economics theory criteria. After a series of econometric tests, the results showed that foreign investment, domestic investment, regional expenditure, exchange rate, Human Development Index, and length of road had a positive and significant effect on Regional Gross Domestic Product. Meanwhile, the total population had an insignificant effect on Regional Gross Domestic Product in Indonesia.